An immune receptor complex evolved in soybean to perceive a polymorphic bacterial flagellin - Wei, Yali; Balaceanu, Alexandra; Rufián Plaza, José Sebastián; Segonzac, Cecile; Zhao, Achen; Morcillo, Rafael J; Macho, Alberto P (Springer Nature, 2020)
In both animals and plants, the perception of bacterial flagella by immune receptors elicits the activation of defence responses. Most plants are able to perceive the highly conserved epitope flg22 from flagellin, the main flagellar protein, from most bacterial species. However, flagellin from Ralstonia solanacearum, the causal agent of the bacterial wilt disease, presents a polymorphic flg22 sequence (flg22Rso) that avoids perception by all plants studied to date. In this work, we show that soybean has developed polymorphic versions of the flg22 receptors that are able to perceive flg22Rso. Furthermore, we identify key residues responsible for both the evasion of perception by flg22Rso in Arabidopsis and the gain of perception by the soybean receptors. Heterologous expression of the soybean flg22 receptors in susceptible plant species, such as tomato, enhances resistance to bacterial wilt disease, demonstrating the potential of these receptors to enhance disease resistance in crop plants.
Keywords: Inmunología vegetal; Ralstonia solanacearum; FLS2; Flagellin; Soybean; Plant immunity